Pengaruh Keharmonisan Keluarga Terhadap Sikap Sosial Anak - Eny Fatimatuszuhro Pahlawati (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2019)
In the field of family education is the main source of education, because all human knowledge and intellectual intelligence is first obtained from parents and family members themselves. On the other hand many roles of mothers have changed, many mothers work outside the home so that many of them entrust the guidance and guidance of their children to an institution that they trust, so that many children today like to argue, disrespectfully, and not obey the existing rules. So this paper aims to describe the Effects of Family Harmony on the Social Attitudes of Children which are examined through several literatures related to the subject, using qualitative descriptive analysis. The influence of family harmony on children's social attitudes is very large, because children who come from harmonious families generally are always open to the surrounding environment, which means having a good social attitude.